Stroke in Mechanical Circulatory Supported Cardiogenic Shock - Galusko, Victor; Panoulas, Vasileios; Gorog, Diana A.; Vandenbriele, Christophe (Thrombosis and Haemostasis, 2025)
Stroke is a devastating and underdiagnosed complication in patients with cardiogenic shock (CS) supported by temporary mechanical circulatory support (tMCS). Stroke occurs in approximately 1 to 4% of patients on microaxial flow pumps and 6 to 7% of those on veno-arterial extracorporeal membrane oxygenation, though the true incidence is likely higher due to diagnostic limitations in sedated and critically ill patients. The occurrence of stroke in this population significantly worsens clinical outcomes, increasing morbidity, mortality, and healthcare resource utilization. This review outlines the risk factors and mechanisms underlying both ischaemic and haemorrhagic stroke in patients receiving tMCS. It explores how the aetiology of CS, the choice of tMCS device, anticoagulation strategies, and cellular injury contribute to stroke risk. The pathophysiology in this setting is multifactorial and often dual-edged, driven by haemolysis, platelet dysfunction, endothelial disruption, and immune-mediated thrombogenesis. Concurrently, bleeding complications arise from acquired von Willebrand syndrome, thrombocytopenia, and dysregulated fibrinolysis. Currently, there are no evidence-based guidelines for managing bleeding and thrombotic complications in patients on tMCS, largely due to the lack of robust data. Consequently, clinical practices vary, and treatment decisions often require navigating a complex balance between thrombosis and bleeding without high-quality evidence to guide care. This review highlights the key physiological and pathological changes associated with tMCS to inform strategies for stroke prevention, early detection, and management. Developing standardised protocols through prospective studies is essential to improving outcomes in this high-risk population.
Keywords: cardiogenic shock; mechanical circulatory support; stroke